PALEOFAUNA DA FORMAÇÃO MALHADA VERMELHA, BACIA DE LIMA CAMPOS, CRETÁCEO INFERIOR, CEARÁ, BRASIL - Passarinho, Isabela Barbosa; Figueiredo, Ana Emilia Quezado de; Fortier, Daniel Costa (Revista Nordestina de Zoologia, 2016)
The sedimentary basins of Iguatu consist of a group of 4 small basins - Iguatu, Lima Campos, Malhada Vermelha and Icó - and are related to the rifting processes between American and African continents. The samples mentioned here are of probable Neocomian age (Lower Cretaceous), coming from Cascudo locality, Icó Municipality, State of Ceará, Lima Campos Basin. The samples were collected in fine sandstone, belonging to the Malhada Vermelha Formation. Ganoid scales and teeth attributed to the genus Lepidotes sp., an angular bone of Mawsonia sp, icnofossis of invertebrates belonging to the ichnogenus Planolites, and conchostracan valves of Palaeolimniopiopsis sp. With such finding, the record of the local conchostracan fauna is expanded. All these materials highlight the paleontological potential of the aforementioned sedimentary basin.